Kemampuan Reproduksi Daphnia magna Jantan Hasil Induksi Logam Berat (Cd, Pb) Dan Pestisida Diazinon [Reproductive Ability Of Male Daphnia magna Induction Results Of Heavy Metal (Cd, Pb) And Pesticide Diazinon] - A. Shofy Mubarak; Desi Nawang Purnamasari; Laksmi Sulmartiwi; Sudarno Sudarno (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
Abstract Daphnia magna is one of the natural food which is used widely in fish hatchery. Generally, Daphnia magna is used widely in larval rearing of fish that are traded in the form of resting eggs called ephipia. Ephipia production can be performed with Daphnia magna culture in conditions that are not optimal, one of which is pollution. If the conditions are not optimal then the parthenogenesis Daphnia magna would produced a male individual. The presence of Daphnia magna males will initiate sexual reproduction, where Daphnia magna males will perform on the female and copulation produce ephipia. Ephipia production is influenced by the efficiency of matting, reproduction ephipia will improve if a high mating eficiency of Daphnia magna. Mating eficiency describes the number of females that successflly fertilized by the male.The purpose of this study is to determine the reproductive capacity of Daphnia magna male's induction of heavy metals (Cd, Pb) and the Pesticide Diazinon on mating efficiency and quality ephipia produced. The research method used is an experimental method by using completely randomized design with 4 treatments and 5 replications so that was followed by Duncan Multiple Range Test. This study uses the ratio of male to female sex 1:30 for each treatment. The treatments in this study consist of control males mated with females, male induced lead (Pb) were mated with female, males induced cadmium (Cd) were mated with females, the male mated with the induction of pesticide Diazinon female. Results showed that treatments using natural male produced an average value of mates which were the highest efficiency and quality ephipia optimal, with precentage of 88,66 and 88,71. So that in order to produce ephipia in large quantities and quality needed natural male culture can be done in the unpolluted waters.